Arginine 37 of Glycine Linker Dictates Regulatory Function of HapR - Ekka, Manjula; Mondal, Abhisek; Singh, Richa; Sen, Himanshu; Datta, Saumen; Raychaudhuri, Saumya (Frontiers in Microbiology, 2020)
HapR is designated as a high cell density quorum sensing master regulatory protein of Vibrio cholerae. It is a member of the TetR family protein and functions both as an activator and a repressor by directly communicating with cognate promoters, thus controlling the expression of a plethora of genes in a density dependent manner. Molecular insights reveal the domain architecture and further unveil the significance of cross talk between the DNA binding domain and the dimerization domain for the functionality of the wild type protein. The DNA binding domain is made up of three α helices where a helix-turn-helix motif spans between the helices α2 and α3. The essentiality of the glycine rich linker linking helices α1 and α2 came into prominence while unravelling the molecular basis of a natural non-functional variant of HapR. Subsequently, the importance of linker length was demonstrated. The present study, involving series of biochemical analyses coupled with molecular dynamics simulation has illustrated the indispensability of a critical arginine within the linker at position 37 contributing to HapR DNA binding activity.